Case‐matched analysis of robotic versus open surgical enucleation for pancreatic tumours: A comparative cost‐effectiveness study. Issue 5 (28th May 2022) - Caruso, Riccardo; Vicente, Emilio; Quijano, Yolanda; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Alfonsel, Javier Nuñez; Malave, Luis; Agresott, Ruben; Ferri, Valentina
Abstract: Background: Enucleation has widely spread as an alternative strategy in the treatment of small pancreatic tumours and cystic lesions. To date there are limited data on perioperative outcomes after pancreatic enucleation performed using a minimally invasive robotic technique, particularly regarding the risk factors associated with postoperative pancreatic fistula (POPF). We perform a comparative study of robotic pancreatic enucleation (RPE) and open enucleation (OPE) with the aim of evaluating clinical and cost‐effective outcomes. Methods: This is a case‐matched analysis of patients who underwent robotic and open pancreatic enucleation performed at Sanchinarro University Hospital, Madrid, from October 2014 to December 2021. Patient data were obtained retrospectively. Clinicopathologic characteristics and perioperative and postoperative outcomes were recorded and analysed. Two groups of demographically similar patients were analysed: the robotic group ( n = 20) and the open group ( n = 20). The patient characteristics of the two groups have been compared. From February 2015, quality‐adjusted life years (QALYs) are also included and prospectively recorded in the database and used to measure the effectiveness of the treatment. Result: A total of 20 RPE and 20 OPE have been included. The incremental cost of the robotic approach versus open was €2617.85(CI 95% 1601.48; 3634.24) and the incremental utility was 0.0879 QALYs (CI 95% 0.0834; 0.0925). The estimated ICER for patients was €29, 782.13 (CI 95% 17, 313.29; 43, 576.01) per QALY gained. Robotic resection resulted a shorter postoperative hospital stay, less wound infections, faster recovery diet and a similar operating time. The two groups had similar complication rates. Pathological data were similar for both procedures. Conclusion: RPE resulted in a shorter hospital stay and less blood loss and morbidity, comparable with the outcomes of open enucleation. RPE may also be acceptable in terms of cost‐effectiveness.